Color and physiochemical attributes of pointed gourd (Trichosanthes dioica Roxb.) influenced by modified atmosphere packaging and postharvest treatment during storage - Hassan, Jahidul; Jahan, Farzana; Rajib, Md. Mijanur Rahman; Sarker, Umakanta; Miyajima, Ikuo; Ozaki, Yukio; Ercisli, Sezai; Golokhvast, Kirill S.; Marc, Romina Alina (Frontiers in Plant Science, 2022)
The efficiency of modified atmosphere packaging (MAP) in combination with postharvest treatment on the shelf-life, physiochemical attributes, color, and nutrition of pointed gourd was studied after storing in refrigerated (low temperature, LT) and ambient (room temperature, RT) conditions. Fresh pointed gourd fruits were dipped in NaOCl solution (0.01% w/v) and potassium metabisulphite (KMS) (0.05% w/v), blanched (100°C for 4 min), and then packed in perforated and non-perforated polythene and polypropylene packets of each type and brown paper bags as MAP before storing at LT and RT. Physiochemical attributes, color, and nutrition were measured until the marketable level of acceptance (up to shelf-life) after storage and compared with the untreated and unpacked samples (control). The results showed profound differences among the treatment variables in all the studied dependent parameters regarding the LT and RT storage conditions. Among the treatments, perforated and non-perforated polyethylene (NPE) and polypropylene (NPP) packaging performed well to retain a considerable amount of ascorbic acid, β-carotene, and greenish color (lower L*, high h*) in pointed gourd treated with NaOCl (0.01%) and KMS (0.05%) after storing at LT and RT. Furthermore, the principal component analysis suggested that five major quality attributes (L*, C*, h*, shelf-life, and ascorbic acid) were influenced remarkably in terms of non-perforated polyethylene packaging in combination with KMS treatment both in LT and RT storage conditions. However, perforated polythene and polypropylene in combination with NaOCl responded well in RT but only for the shortest storage life. Thus, a non-perforated polythene package with KMS treatment would be the best solution for retaining market quality acceptance with green color up to the extended shelf-life of 23 and 10 days, respectively, in the refrigerator (LT) and in ambient (RT) storage conditions.